Synthesis, Characterization and Antifungal Effects of Silver Nanoparticles of Ageratum Conyzoides L. - Moustafa, Mahmoud; Sayed, Mahmoud; Alamri, Saad; Alghamdii, Huda; Shati, Ali; Alrumman, Sulaiman; khatani, Mohmed Al; Qthanin, Rahma Al; Siddique, Sajda; Ahmed, Dalia; Negm, Sally; Emam, Ahmed Al (Bangladesh Journal of Botany, 2022)
Synthesis and characterization of silver nanoparticles (AgNPs) produced from Ageratum conyzoides leaves extract, as well as their antifungal effectiveness against a variety of plant pathogens were investigated. Absorption peaks at 3674, 3264, 2980, 2940, 2096, 1739, 1545, 1370, 1080 and 700 cm−1 were recorded for the formed nanoparticles using FTIR analysis. According to SEM, XRD and UV spectroscopy results, nanoparticles have spherical and semi- spherical shape, size of 34 to 205 nm with a resonance wavelength at 460 nm. Ageratum conyzoides-AgNPs showed moderate antifungal activity against Penicillium expansum, Macrophomina phaseolina, Alternaria alternata, Drechslera halodes and Fusarium oxysporum f.sp. lycopersici. The fabricated NPs from leaves of A. conyzoides can be applied as antifungal agent. Bangladesh J. Bot. 51(3): 439-444, 2022 (September)